TeleMed LAN-based patient monitoring system on Linux Platform - Ancajas, Norman B. (2007)
A telemedical system allows patients to seek help from doctors situated on remote areas and receive reliable medical advice. Remote patient monitoring is used in situations where there might be a rapid deterioration in a patient's medical condition by identifying a subject's vital signs. Advantages for these processes include faster medical response and wider access to quality healthcare. We have implemented a telemedical system that operates over a local area network. The system is composed of a Data Acquisition (DAQ) Unit and two client computers connected in the network. The DAQ involves interfacing biomedical signals taken from two modules, an electrocardiogram (ECG) module previously developed by the IRC laboratory and the commercially-available BCI 3301 pulse oximeter. The Zilog Z8F6401 microcontroller is used to perform analog-to-digital signal conversion and data transfer from the modules to a client computer (called the Rx Box) using serial communications. A GUI program in the Rx Box displays the received data and transmits it to another client computer (called the Doctor's Workstation) where it is also displayed. Both client computers run on Ubuntu, a Debian-based Linux distribution. Instant messaging (IM) and videoconferencing features are implemented from existing open-source applications to provide user interaction. A local IM server is set-up to handle connections between the clients in the local area network.